Effects of Nanoscale Carbon Black Modified by HNO3 on Immobilization and Phytoavailability of Ni in Contaminated Soil - Jiemin Cheng; Lei Yu; Tong Li; Yuzhen Liu; Chengxiu Lu; Tingting Li; Hanwei Wang (Journal of Chemistry)
A surface-modified nanoscale carbon black (MCB) as Ni adsorbent in contaminated soil was prepared by oxidizing the carbon black with 65% HNO3. The surface properties of the adsorbent were characterized by zeta potential analysis, scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIRs). Batch experiments were conducted to evaluate the improvement of Ni2+ adsorption by MCB. Greenhouse cultivation experiments were conducted to examine the effect of MCB on the DTPA-extractable Ni2+ in soil, Ni2+ uptake of ryegrass shoot, and growth of ryegrass. Results indicated that MCB had much lower negative zeta potential, more functional groups for exchange and complexation of cation, and more heterogeneous pores and cavities for the adsorption of cation than the unmodified parent one (CB). MCB showed enhanced sorption capacity for Ni (qmax, 49.02 mg·g−1) compared with CB (qmax, 39.22 mg·g−1). Greenhouse cultivation experiment results showed that the biomass of ryegrass shoot and the Ni uptake of the ryegrass shoot were significantly increased and the concentrations of DTPA-extractable Ni in soil were significantly decreased with the increasing of MCB amount. It is clear from this work that the MCB had good adsorption properties for the Ni and could be applied in the in situ immobilization and remediation of heavy metal contaminated saline-alkali soils.